A 2014 Update on Coagulation Management for Cardiopulmonary Bypass. (June 2014) - Thiele, Robert H.; Raphael, Jacob
Coagulopathy after cardiac surgery with cardiopulmonary bypass is a serious complication that may result in massive bleeding requiring transfusion of significant amounts of blood products, plasma, and platelets. In addition to increased patient morbidity and mortality it is associated with longer hospital stay and increased resource utilization. The current review discusses aspects in cardiopulmonary bypass–induced coagulopathy with emphasis on point-of-care testing and individualized "goal-directed" therapy in patients who develop excessive bleeding after cardiac surgery.